(untitled) (Journal of Surgical Sciences, 2020)
Background: Carcinoma of the stomach is a major cause of cancer mortality worldwide. Due to social impact of gastric carcinoma (GC), there is a need to stratify patients into appropriate screening, surveillance and treatment programs. Although histopathology remains the most reliable and less expensive method, numerous efforts have been made to identify and validate novel biomarkers to accomplish the goals. In recent years, several molecules have been identified and tested for their clinical relevace in GC management. Among the biomarkers with the exception of HER2, none of the biomarkers is currently used in clinical practice, and some of them were described in single studies. Materials and Methods: This prospective type of observational study was performed in the Department of Surgery, Dhaka Medical College Hospital, Dhaka, 6 months from approval of protocol. Total 45 consecutive patients aged 18 years and above without consideration of gender were selected purposefully. Every patient was evaluated by clinical examination, appropriate investigations and after a confirm diagnosis of the tissue from the cancer. All patients have undergone operative intervention and Gastrectomy specimens were subtotal (including cardiac and pylorus), subtotal (including the pylorus), total radical gastrectomy and oesophago-gastrectomy sample. All specimens obtained were immersed in 10% formalin. Samples of whom were sent to the department of pathology, DMCH for histopathology examination. Portion of representative tissue/block was sent to AFIP (Armed Forces Institute of Pathology, Dhaka) for immunohistochemistry to find out the HER2 expression in gastric cancer and gastro-oesophageal cancer. Data was collected in a pre-designed questionnaire by face to face interview. Result and observation: In this study when 45 cases were categorized according to WHO grading system it was observed that majority (30) patients were found in grade II, among them 3(10%) were HER2 positive. But with grade III tumour the HER2 positivity were found more i,e; 37.5% (3/8). Grade- I tumor show HER2 neu expression 28.57% (2/7) and according to location most of the cases with HER2 positive expression was located in the gastro-esophageal junction which is 27.27% (3/11) than gastric carcinoma which is 14.70% (5/34). Conclusion: Most of the patients of gastric and gastrooesophageal junction adenocarcinoma are diagnosed at a very late stage, so they require special attention in treatment protocol, including chemotherapy and immunotherapy for increasing their survivability. The study showed with poorly differentiated (high grade) tumour, the HER2 positivity were found more. Journal of Surgical Sciences (2018) Vol. 22 (2) : 79-82